Cultivar la empatía a través de las humanidades: reflexión sobre una experiencia pedagógica en el aula universitaria (2016)
The role of the Humanities in higher education is fundamental for the formation of integral professionals. They are also essential for he construction of functional citizens in a democratic society. These individuals have abilities and capacities by which they can be defined as citizens of the world (Martha Nussbaum, 1997), and these need to be cultivated in the light of all social aspects. As such, the educational models and the academic institutions must contribute to the development of society through the “cultivation” of the Humanities. The following article is a reflection about the pedagogical experience in the context of the University, based on some ideas put forward in Martha Nussbaum’s educational proposal.